Megavolt nanosecond 50 kW average power all-solid-state driver for commercial applications; The 10th IEEE International Pulsed Power Conference, Albuquerque, New Mexico, july 3-6, 1995 - Kotov Yu. A.; Mesyats G. A. Gennady Andreyevich; Rukin S. N.; Telnov V. A.; Slovikovskii B. G.; Timoshenkov S. P.; Bushyakov A. I. (1995, 1995)
В фонде НТБ ТПУ отсутствует